`(x+y)^3=x^3+y^3`

Differentiating both sides with respect to x,

`3(x+y)^2d/dx(x+y)=3x^2+3y^2dy/dx`

`3(x+y)^2(1+dy/dx)=3x^2+3y^2dy/dx`

`3(x+y)^2+3(x+y)^2dy/dx=3x^2+3y^2dy/dx`

`((x+y)^2-y^2)dy/dx=x^2-(x+y)^2`

`(x^2+y^2+2xy-y^2)dy/dx=(x^2-x^2-y^2-2xy)`

`(x^2+2xy)dy/dx=(-y^2-2xy)`

`dy/dx=(-y^2-2xy)/(x^2+2xy)`

Derivative at point (-1,1) can be found by plugging in the values of (x,y) in dy/dx.

Therefore derivative at point (-1,1)=`(-1^2-2(-1)(1))/(1^2+2(-1)(1))`

`Derivative = -1`

` `

## See

This Answer NowStart your **48-hour free trial** to unlock this answer and thousands more. Enjoy eNotes ad-free and cancel anytime.

Already a member? Log in here.

`(x+y)^3=x^3+y^3`

Differentiating both sides with respect to x,

`3(x+y)^2d/dx(x+y)=3x^2+3y^2dy/dx`

`3(x+y)^2(1+dy/dx)=3x^2+3y^2dy/dx`

`3(x+y)^2+3(x+y)^2dy/dx=3x^2+3y^2dy/dx`

`((x+y)^2-y^2)dy/dx=x^2-(x+y)^2`

`(x^2+y^2+2xy-y^2)dy/dx=(x^2-x^2-y^2-2xy)`

`(x^2+2xy)dy/dx=(-y^2-2xy)`

`dy/dx=(-y^2-2xy)/(x^2+2xy)`

Derivative at point (-1,1) can be found by plugging in the values of (x,y) in dy/dx.

Therefore derivative at point (-1,1)=`(-1^2-2(-1)(1))/(1^2+2(-1)(1))`

`Derivative = -1`

` `